Measuring Blue Ocean Leadership activities in public organizations: field research in the Ministry of Communications - Mustafa AbdulAbbas Assad; Reyam Qasim Mohammed (Technium Business and Management, 2024)
This study aims to identify the level of application of blue ocean leadership activities in public organizations and to build a conceptual and cognitive framework around this concept. The study adopted a descriptive-analytical approach, and the research sample consisted of (95) individuals from the senior management working at the center of the Iraqi Ministry of Communications (director general, department manager, section head). The data analysis technique used is structural equation modeling (SEM) and the Statistical Package for the Social Sciences (SPSS). The results indicate that the senior management in the Ministry of Communications is working to adopt the blue ocean leadership style through its activities, but not to the level that highlights the role of this leadership style and its importance in achieving gains and leadership goals, by coordinating the efforts of employees and extracting the best of their ideas and innovative solutions that add value to the services provided by the ministry. This study differs from previous studies in that it was studied at the level of the public sector, and it examines the level of availability of blue ocean leadership activities in public organizations.